When clubbing isn’t just clubbing: genetically proven primary hypertrophic osteoarthropathy in a child - Kolhe, Vrushali M.; Jahagirdar, Rahul R.; Deshpande, Ruma M.; Datar, Chaitanya A. (International Journal of Contemporary Pediatrics, 2025)
Hypertrophic osteoarthropathy (HOA) is a rare syndrome characterized by digital clubbing, periostosis and arthropathy. It manifests as abnormal proliferation of the skin, soft and osseous tissues in the distal parts of extremities. The disease can be classified into two forms: primary and secondary. Primary hypertrophic osteoarthropathy is most often autosomal recessive, though autosomal dominant and sporadic cases are described. Pathogenic variants in HPGD and SLCO2A1—key regulators of prostaglandin metabolism—lead to elevated prostaglandin E2 levels, causing abnormal bone and soft tissue proliferation. Secondary hypertrophic osteoarthropathy is linked to a variety of pulmonary, cardiac, and other systemic conditions. Herein this report presents a case of an 18-year-old male who presented with progressive grade 4 clubbing, varicosities of the right lower limb, bilateral lower limb pain and exertional breathlessness since early childhood. Examination revealed craniofacial dysmorphism, bulbous fingertips and toes, clinodactyly and chest deformity. Radiographs demonstrated acro-osteolysis with prominent bones. Laboratory parameters were largely normal except for mildly elevated parathyroid hormone and erythrocyte sedimentation rate (ESR). Echocardiography was normal. Genetic analysis identified a homozygous missense variant in exon 4 of the HPGD gene, confirming the diagnosis of primary hypertrophic osteoarthropathy. This case highlights the importance of considering genetic causes in pediatric patients presenting with unexplained clubbing and skeletal deformities. Early recognition of primary HOA can prevent unnecessary evaluation for secondary causes and guide genetic counseling.